Designing a Railway Ticket Ordering Information System at PT Hotel Murah Travelindo Jakarta With Waterfall Method - Oktaviani, Anggi; Susanti, Melan; Sarkawi, Dahlia; Adriani, Tiara (Politeknik Ganesha Medan, 2019)
PT Hotel Murah Travelindo needs a information system that supports and provides satisfying services for customers. At this time PT. Hotel Murah Travelindo or commonly called Hotel Murah is one of the largest hotel providers in Indonesia that provides hotel bookings throughout Indonesia and Southeast Asia. The system at PT. Hotel Murah Travelindo has been computerized, starting from recording customer data that booked hotels, to storing other data related to the order process to making hotel vouchers, thus minimizing during the process of recording errors. Until now, new Hotel Murah Travelindo provide hotel bookings online. PT. Hotel Murah Travelindo wants to develop train ticket reservations online. The design of this information system is the best solution to solve the problems that exist in purchasing train tickets that are always exhausted, and with a computerized system can be achieved an activity that is effective and efficient in supporting the activities of this company